Comprehensive Insight into Cutaneous Application of Hemp - Ana Žugić; Milica Martinović; Vanja Tadić; Miloš Rajković; Gordana Racić; Ivana Nešić; Anamarija Koren (MDPI AG, 2024)
Known for its natural bio-compounds and therapeutic properties, hemp is being utilized in the development of skin products. These products offer a wide range of applications and benefits in the fields of natural bio-compounds, pharmaceutical technology, topical delivery systems, and cosmeceuticals. This manuscript deals with hemp actives, such as cannabinoids, terpenes, and flavonoids, and their diverse biological properties relative to topical application, including anti-inflammatory, antimicrobial, and antioxidant effects. Also, the paper reviews strategies to overcome poor penetration of hemp actives, as well as the integration of hemp actives in cosmeceuticals that provide natural and sustainable alternatives to traditional skincare products offering a range of benefits, including anti-aging, moisturizing, and soothing properties. The review aims to provide a comprehensive understanding of the development and manufacturing processes of skin products containing hemp actives. By delving into the science behind hemp-based products, the paper provides valuable insights into the potential of hemp as a versatile ingredient in the pharmaceutical and cosmetic industries. The utilization of hemp in these innovative products not only offers therapeutic benefits but also promotes natural and sustainable approaches to skincare.